Meningococcemia in an 11 Months Old Infant - Rachana Shrestha; Saurab Karki; Manoj Khadka; Suhail Sapkota; Bibek Timilsina; Sulochana Khadka (Case Reports in Infectious Diseases)
Meningococcemia is the infection of the blood caused by Neisseria meningitidis. Herein, we report a case of meningococcemia in an 11 months old infant who had a high-grade fever, nonblanching purpuric rash over the face and limbs, low blood pressure, tachycardia, and prolonged capillary refill time, but without neck rigidity and focal neurologic signs. He recovered after supportive care and treatment with antibiotics (intravenous ceftriaxone, vancomycin, and teicoplanin). Therefore, in a febrile, ill-looking child in shock with a nonblanching rash, meningococcal disease should be suspected. The study shows the importance of vaccination against meningococcal disease.